(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The 21st century has witnessed the influx of information in electronic format which has increased library’s responsibility of embracing digital preservation. Failure of which is liable to be the cause of the deterioration observed. The aim of the study is to, among several other reasons, explore, the influence of institutional support and digital competence on preservation and conservation practices among library personnel. The descriptive survey research design was adopted for the study. Questionnaire with 0.73, 0.68 and 0.82 Cronbach alpha reliability rate was used for data collection. The study population is made up of One hundred and Ninety library personnel. The data collected was analysed using both descriptive and inferential statistics. The study found that preservation is highly practiced (Mean = 3.4), institutional support was found to be high (Mean = 3.1). However, the study found deficiencies in the areas of automation/maintenances and provision of infrastructural facilities with a moderate mean score of 2.61 and 2.3. The test of hypotheses further revealed that institutional support has significant influence on digital preservation (Adj. R2=0.076, F (1,164)= 15.219,p =0.000b). The study confirmed a commendable level of institutional support within academic libraries. However, a notable gap was identified in the automation of processes and the provision of necessary technological infrastructure. This gap represents an area where further attention and investment are needed to fully harness the potential of digital preservation and conservation efforts. The study recommends that Academic institutions should prioritize the preservation and conservation of digital resources as well as physical resources.